ESTABLISHMENT OF CRITERIA FOR ESTIMATION THE PUBLIC HEALTH ACCEPTABILITY AND THE QUALITY STANDARDIZATION OF THE YOGURT - ΣΚΟΥΝΤΖΟΣ, Κ.; ΠΑΠΑΔΙΑ, Α.; ΠΑΠΑΣΤΑΥΡΟΥ, Θ.; ΠΑΝΑΓΙΩΤΟΠΟΥΛΟΣ, Ν. (Journal of the Hellenic Veterinary Medical Society, 1973)
During the years 1971 and 1972, 455 yogourt samples produced from cow and sew milk in the districts of Athens and Thessaloniki, were examined. From the industrially produced yogurt 11,1% of the samples were found carrying a high E. coli content, while in small entreprises the percentage was 21,6%. No samples with coagulase and D—Ν—Ase positive staphylococcus species were detected. Extreme Soxhlet-Hankel acidity values appeared largely fluctuating from the mean value. The product is not standardised. Criteria for quality standardization and public health acceptability are suggested.